The Effect of Entrepreneurial Orientation on Competitive Advantage with Product Innovation as a Mediation Variable - Iklima Septiani; Tetty Sufianty Zafar; Sopyan Saori (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The rapid growth of the coffee shop industry in Sukabumi City has created increasingly fierce business competition. To face these challenges, business actors need to have superior strategies supported by entrepreneurial orientation and product innovation. This study aims to analyze the effect of entrepreneurial orientation on competitive advantage with product innovation as a mediating variable. This study uses a quantitative approach with a census technique on 42 coffee shop owners in Sukabumi City. Data collection was carried out through a questionnaire using a Likert scale, and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method using SmartPLS software. The results show that entrepreneurial orientation has a significant effect on product innovation, and product innovation has a significant effect on competitive advantage. In addition, product innovation has been proven to significantly mediate the relationship between entrepreneurial orientation and competitive advantage. These findings indicate that the success of coffee shops in building competitive advantage is greatly influenced by the extent to which business owners are able to implement entrepreneurial orientation innovatively in product development.